Terry's nails: A sign of systemic disease - Anna B Witkowska; Thomas J Jasterzbski; Robert A Schwartz (Wolters Kluwer Medknow Publications, 2017)
Terry's nails are a type of apparent leukonychia, characterized by ground glass opacification of nearly the entire nail, obliteration of the lunula, and a narrow band of normal, pink nail bed at the distal border. The aim of this study is to guide clinical practice by reviewing all of the data concerning Terry's nail that have become available since the original description by Terry in 1954, with particular reference to all clinical features, associated medical conditions, pathogenesis, and necessary workup. PubMed was searched using the keywords "leukonychia" and "Terry nails." Although the abnormality can occur with normal aging, Terry's nails can also be an indication of an underlying medical condition, most notably, cirrhosis, chronic renal failure, and congestive heart failure. A change in nail bed vascularity, secondary to overgrowth of connective tissue, is thought to be responsible, with nail bed biopsy revealing telangiectasias in the distal band. The differential diagnosis for Terry's nails includes half-and-half nails (Lindsay's nails), Muehrcke's nails, and true leukonychia totalis/partialis. Having the ability to delineate these nail findings can be a valuable tool in clinical practice as each entity is associated with a different set of systemic conditions. Terry's nails highlight the intimate connection between nail changes and systemic disease as well as the importance of thorough nail inspection with every physical examination.